Soil-structure interaction influence on the design of spread footing foundations in a reinforced concrete building - Yago Ryan Pinheiro dos Santos; Denney Wesley da Silva; Joandson Dyego da Silva (Discover Civil Engineering)
Abstract The study aims, through soil-structure interaction analyses, to examine its influence on a shallow foundations design of a building in reinforced concrete on a bedrock terrain. For the analyses, the foundation elements were calculated considering the rigid and flexible building supports—the latter represented such interaction by spring coefficients “K”, obtained by the ratio between the loads obtained in each pillar and the settlements suffered by them obtained via monitoring in the field. Comparisons between projects consisted of changes in element geometry and material consumption of the 14 isolated and 2 associated footings. The greatest changes in the footing geometry were observed in the length of SB03 (reduction of 15 cm) and in the width of SB06 (reduction of 10 cm) and SB08 (increase of 10 cm), while, when considering the area as a whole, SB06 presented the greatest reduction (7.48 m2 to 6.93 m2). Concrete volume was the most influenced by redistribution, implying changes of around 18% for SB06, but maintained the total volume of concrete required to execute the project for all foundation elements, due to compensation for geometry changes and material consumption between the relieved and increased load footings. Factors such as the interaction between components, terrain deformability, asymmetry in building plans, and more and less loaded pillar locations influence the interaction and, consequently, the foundations' design. Emphasizes the importance of soil-structure interaction studies, which contribute to executing projects with greater safety and better performance, meeting the real field conditions.